Level of Basic Skills for Playing Futsal of Students in the Faculty of Sports Science, Makassar State University - Akbar Sudirman (PT FORMOSA CENDEKIA GLOBAL, 2022)
ABSTRACT: This article is expected to provide an overview of the level of futsal playing skills of students of the Department of Physical Education, Health and Recreation (PJKR) Faculty of Sports Science (FIK) Makassar State University (UNM). So that through this article, it is hoped that it can also be used as a guide to improving the basic skills of playing futsal for students. This research is descriptive and quantitative with one variable without making comparisons and without connecting with other variables. The method used in this research is a survey. This survey was conducted to determine the level of futsal playing skills of students majoring in Physical Education, Health, and Recreation, Faculty of Sports Science, Makassar State University. The skill test used involves several basic techniques including dribbling, passing, control, and shooting. Based on the results of the study, it was obtained that the score of the futsal playing skill level of the PJKR FIK UNM students was 5 students (5%) declared very good, 32 students (32%) declared good, 32 students (32%) were declared sufficient, 26 students (26%) were declared poor. , and 5 students (5%) stated less once. While the average value of 60.59 seconds is at the interval of 54.95 < X 66.24, the level of futsal playing skills of the PJKR FIK UNM 2019 students is considered sufficient.